2020
DOI: 10.1016/j.heliyon.2020.e04174
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analyses on effective removal of cadmium and hexavalent chromium ions by multiwall carbon nanotubes (MWCNTs)

Abstract: In this work, multiwall carbon nanotubes (MWCNTs) developed from cobalt-ferrite catalyst on activated carbon (from castor seed), was used as an adsorbent for the removal of cadmium and hexavalent chromium ions. The effectiveness of the adsorbent for the uptake of Cd(II) and Cr(VI)ions from aqueous solution was investigated in a process batch adsorption study. The developed activated carbon and MWCNTs were characterized by Brunauer-Emmett-Teller (BET) surface area analysis, Fourier Infrared Spectroscopy (FT-IR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…To predict the best kinetic and isotherm model which describes better the adsorption of cadmium and lead ions onto CaCEPPA and CoCEPPA materials, four error functions were applied: correlation coefficient R 2 ; sum of squares of the errors ERRSQ (Equation (9)); chi-square test χ 2 (Equation (10)); average relative error ARE (Equation (11)) [ 59 , 60 , 61 , 62 ]. …”
Section: Methodsmentioning
confidence: 99%
“…To predict the best kinetic and isotherm model which describes better the adsorption of cadmium and lead ions onto CaCEPPA and CoCEPPA materials, four error functions were applied: correlation coefficient R 2 ; sum of squares of the errors ERRSQ (Equation (9)); chi-square test χ 2 (Equation (10)); average relative error ARE (Equation (11)) [ 59 , 60 , 61 , 62 ]. …”
Section: Methodsmentioning
confidence: 99%
“…CBB showed the presence of whitish particles and sticky structures on the biochar surface. This might be due to incomplete combustion during the carbonization process in the muffle furnace [47]. CBB also showed more coarse and compacted characteristics, including few pores and cavities.…”
Section: Scanning Electron Microscope (Sem) Analysismentioning
confidence: 98%
“…This observed morphology must have been attributed to countless volatile components in the form of organic matter and impurities present in the biochar before activation Organic matter decomposition during carbonization process however, must have led to the escape of several volatile components in the biochar which must have resulted into it having such morphology [48]. .Also the heterogeneous surface nature, and irregular shape of CBB suggests its efficient feasibility in the coagulation of heavy metals and organic pollutants [47].…”
Section: Scanning Electron Microscope (Sem) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid advancement of material science, newer adsorbents with high adsorption capacity, cost effectiveness, eco-friendliness, and selectivity are being reported ( Hashem et al., 2021 ). Several research works have reported the use of different materials beginning with chitosan ( Zarghami et al., 2016 ), clay ( Obayomi and Auta, 2019 ), silica ( Radi et al., 2019 ) zeolites ( Cheng et al., 2021 ), carbon nanotubes ( Khan et al., 2021 ), multiwall carbon nanotubes ( Obayomi et al., 2020 ), metal organic framework ( Ahmadijokani et al., 2021 ), and covalent organic framework ( Xiao et al., 2021 ) amongst others to be utilized as an adsorbent for the treatment of heavy metal pollutants in wastewater. Low sorption and desorption efficiency, unstable chemically at low pH, low selectivity and cost effectiveness are the challenges associated with the aforementioned adsorbents ( Obayomi et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%